Sustainable Community Development through Homestay Programme - Dayang Affizzah, Awang Marikan; Melissa, W.; Muhammad Ashraf, R. (Macrothink Institute, 2017)
This study analyses the dimensionality of tourist perceived value in community-based homestay tourism context. A survey of 150 visitors to homestay in Kuching, Sarawak was conducted and used to examine the perceived value dimensions in tourism context, statistical analysis and structural equation model were used to verify the validity and reliability of scales used. Satisfaction Level was measured using tested perceived value with six dimensions that illustrated through structural construct, (i) emotional value, (ii) experiential value (host-guest interaction), (iii) experiential value (activity, culture and knowledge), (iv) functional value (establishment), (v) functional value (price), and (vi) functional value (service). The finding shows that emotional, experiential and functional are important determinants of perceived value which affect the visitor’s satisfaction level on homestay tourism. Moreover, statistical findings indicated that only five dimensional have positive affect towards Satisfaction Level while function value (establishment) computed a negative affect towards satisfaction.